Investigation of the antiviral activity of an oral drug preparation based on immobilized interferon λ-1 - D. N. Kinsht; P. G. Madonov; G. V. Kochneva; T. S. Tartynova; G. I. Baykalov (Сибирский научный медицинский журнал, 2019)
Despite the success in developing direct-acting antiviral drugs, in routine clinical practice the use of interferons remains relevant. Parenteral administration of interferons is accompanied by systemic side effects and presents significant inconveniences for patients. A drug based on interferon λ-1, which has high enteric bioavailability and ensures its high concentration in the liver, is promising for the effective treatment of hepatotropic viruses. The aim of the investigation was to study the antiviral activity of an oral medicine based on interferon λ-1 immobilized on polyethylene glycol-1500 by electron-beam synthesis technology. Materials and methods: Real time PCR, Western blot and immunohistochemical method were used to study antiviral activity of tested medicine against hepatitis C virus. Results and discussion: The tested medicine retains antiviral activity against hepatitis C virus. All obtained results are consistent with each other. A 50 % inhibitory dose is in the range of 0.008-0.08 ng/ml. Conclusion: IFN λ-1 immobilized on polyethylene glycol with the help of radiation synthesis technology can be considered as a prototype of an oral drug for the treatment of viral hepatitis, in particular hepatitis C.